2020
DOI: 10.1016/j.xinn.2020.100061
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis and Monitoring the Viral Shedding of SARS-CoV-2 Infection

Abstract: The global pandemic of Coronavirus Disease 2019 (COVID-19) is now ongoing. Rapid and accurate detection of the causative virus SARS-CoV-2 is vital for the treatment and control of COVID-19. In this study, the comparative sensitivity of different respiratory specimens were retrospectively analyzed using 3552 clinical samples from 410 Guangdong CDC (Center for Disease Control and Prevention) confirmed COVID-19 patients. Except for BALF, the sputum possessed the highest positive rate (73.4%∼87.5%), followed by na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
163
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(174 citation statements)
references
References 33 publications
3
163
0
8
Order By: Relevance
“…SARS-CoV-2 RNA can be detected in both upper and lower respiratory specimens including nasal swab, oropharyngeal swab, sputum, and bronchoalveolar lavage fluid (BALF). 2 , 3 Despite BALF, which is not a requisite for COVID-19 diagnosis because of the harder sampling, the sputum was reported to have the highest positive rate (74.4–88.9%), followed by nasal swabs (53.6–73.3%) during the first 14 days after onset (d.a.o.). 3 The positive rate for throat swab was reported to be around 60%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 RNA can be detected in both upper and lower respiratory specimens including nasal swab, oropharyngeal swab, sputum, and bronchoalveolar lavage fluid (BALF). 2 , 3 Despite BALF, which is not a requisite for COVID-19 diagnosis because of the harder sampling, the sputum was reported to have the highest positive rate (74.4–88.9%), followed by nasal swabs (53.6–73.3%) during the first 14 days after onset (d.a.o.). 3 The positive rate for throat swab was reported to be around 60%.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Despite BALF, which is not a requisite for COVID-19 diagnosis because of the harder sampling, the sputum was reported to have the highest positive rate (74.4–88.9%), followed by nasal swabs (53.6–73.3%) during the first 14 days after onset (d.a.o.). 3 The positive rate for throat swab was reported to be around 60%. 3 , 4 Viral RNA is also detected in serum samples with a percentage of 0% (0/31), 5 8% (1/12), 6 or 15% (6/41).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic testing is a cornerstone of the COVID-19 pandemic response strategy [1], yet the establishment of laboratory testing which is accurate, practical, and scalable to meet the demand for public health surveillance measures has been a considerable challenge. Nasopharyngeal swabs are the preferred specimen type over throat swabs due to superior sensitivity [2,3], and over nasal aspirates due to lower risk of aerosol generation. Flocked nasopharyngeal swabs are designed to maximize mucosal contact and more efficiently release contents into the testing medium [4,5]; however, due to global demand during the pandemic response, a reliable supply of high-quality, flocked swabs and appropriate viral transport medium has been difficult to procure.…”
Section: Introductionmentioning
confidence: 99%
“…They also pointed out that, for severe cases, most required is detection of virus in bronchoalveolar lavage. 5 Serological tests detect antibodies to SARS-CoV-2 and in that way identify individuals who were in contact with virus. It was even suggested that combining RT-PCR with serological tests is optimal for diagnosis of suspected patients.…”
Section: Introductionmentioning
confidence: 99%